Faktor Risiko Kejadian Stunting pada Anak Usia 9-24 Bulan di Wilayah Kerja Puskesmas pada Kecamatan Dullah Utara Kota Tual Tahun 2022 - Alfaro Muhammad; Zubaedah Hehanussa; Josepina Mainase (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is one of the growth disorders that occur in childhood under two years. Stunting events can be influenced by two factors, namely direct factors and indirect factors. Based on data from the Tual City Health Office, the number of stunting cases in Tual City was recorded in 2021 as many as 308 cases and 74 cases in North Dullah District. The purpose of this study is to find out the picture of risk factors for stunting events in children aged 9-24 months in the puskesmas work area in North Dullah District of Tual City for the period 2021. This research is quantitative research, a type of observational descriptive research with a cross sectional design. The sample in this study was children aged 9 months to 24 months who experienced stunting and domiciled in North Dullah District for the 2021 period as many as 71 children and then given questionnaires to be filled out. The data obtained is presented in the form of a table accompanied by explanations and arranged and grouped according to the purpose of the research. The results showed that in the North Dullah Health Center of Tual City, as many as 71 children aged 9-24 years experienced stunting, as many as 47 stunting children (66.2%) aged 9-24 months did not experience BBLR (not at risk), the sex of stunting children aged 9-24 months who were most found was male, namely as many as 47 children (66.2%), most children did not get exclusively breast milk, namely as many as 45 children (63.4%) and most children were immunized as many as 41. children (57.7%). The most maternal education level is high school as many as 32 people (45.1%) and many parents' incomes are in the low category of 68 cases (95.8%).